2009
DOI: 10.1007/s00442-009-1519-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of plant architecture versus leaf quality on attack by leaf-tying caterpillars on five oak species

Abstract: Because shelter-building herbivorous insect species often consider structural features of their host plants in selecting construction sites, their probability of attack is likely to be a function of some combination of plant architectural traits and leaf quality factors. We tested the hypothesis that plant architecture, in the form of the number of touching leaves, influences interspecific variation in attack by leaf-tying caterpillars in five species of sympatric Missouri oaks (Quercus). We compared colonizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 15 publications
5
42
0
Order By: Relevance
“…While arthropod diversity and abundance in artificial leaf ties had opposite correlations with foliar total phenolics contents (negative for 1/D and positive for abundance), neither measurement was correlated with leaf width. This is consistent with the findings of Marquis and Lill (2010), where natural leaf-tie formation was demonstrated to be correlated with foliar chemical traits including nitrogen availability and protein-binding capacity, but not physical traits such as leaf toughness and specific leaf area. These chemical traits contributed significantly to different natural leaftie densities among five species of oaks (Q. alba, Q. muehlenbergii, Q. stellata, Q. velutina, and Q. rubra) (Marquis and Lill 2010), potentially affecting inquiline arthropod abundance and richness on these trees.…”
Section: Discussionsupporting
confidence: 92%
“…While arthropod diversity and abundance in artificial leaf ties had opposite correlations with foliar total phenolics contents (negative for 1/D and positive for abundance), neither measurement was correlated with leaf width. This is consistent with the findings of Marquis and Lill (2010), where natural leaf-tie formation was demonstrated to be correlated with foliar chemical traits including nitrogen availability and protein-binding capacity, but not physical traits such as leaf toughness and specific leaf area. These chemical traits contributed significantly to different natural leaftie densities among five species of oaks (Q. alba, Q. muehlenbergii, Q. stellata, Q. velutina, and Q. rubra) (Marquis and Lill 2010), potentially affecting inquiline arthropod abundance and richness on these trees.…”
Section: Discussionsupporting
confidence: 92%
“…In the case of arthropod associated to oak species, several studies have supported the hypothesis proposed by Mattson Jr. (1980); these studies found a positive relationship between leaf nitrogen concentration in Q. alba (Wold and Marquis 1997), Q. prinus, Q. rubra (Forkner and Hunter 2000), Q. dentata (Nakamura et al 2008), Q. geminata, Q. laevis Stiling 2006, 2008), Q. alba, Q. coccinea, and Q. velutina (Marquis and Lill 2010) and the density of herbivorous insects (i.e., leaf miners, leaf-chewing, gall-forming, and leaf rollers). Similarly, it has been reported that higher leaf nitrogen content in Q. crispula favors greater species richness of leaf-chewing insects (Lepidoptera) (Murakami et al 2005(Murakami et al , 2008.…”
Section: Chemistry Of the Host Plantmentioning
confidence: 66%
“…In general, there are records of a significant effect of the individual plant species on the concentration of nitrogen and secondary metabolites (Laitinen et al 2000;Osier et al 2000;Cornelissen and Stiling 2008;Marquis and Lill 2010), suggesting that such variability affects the foraging activity and spatial distribution of arthropods. It has been suggested that the variation in the concentration of nitrogen and secondary metabolites depends on the following: (1) the genotype of the host plant (Glynn et al 2004), (2) environmental conditions (Larsson et al 1986;Henriksson et al 2003;Niinemets and Kull 2003), and (3) the resources of the host plant (Ricklefs 2008).…”
Section: Chemistry Of the Host Plantmentioning
confidence: 99%
“…Although studies have found similar numbers of lepidopteran larvae among tree species (Butler and Strazanac, 2000;Summerville et al, 2003;Turčani et al, 2010), individual Lepidopera species often specialize on host trees. For example, tree species such as Q. alba can contain five times the number of leaf-tying Lepidoptera compared to other oak species (Marquis and Lill, 2010). Leaf chemistry also can influence herbivorous insects, including nitrogen (Koricheva et al, , 2007-2009.…”
Section: Discussionmentioning
confidence: 98%